Implementing Remote CLIL during the Covid-19 Pandemic: A Teacher’s Voice - Sri Setyarini; Vina Nuzulul Fitria; Nissa Khairunnisa; Susilawati Susilawati (Jurnal Pendidikan Bahasa dan Sastra, 2023)
Delivering content and language at the same time is believed to equip students with excellent and balanced competence. The goal of this study is to investigate and describe the implementation of CLIL (Content and Language Integrated Learning) in an English class during the COVID-19 pandemic. A qualitative case study design was employed in this research. The participant in the study is an English teacher at a private junior high school in Cimahi, West Java, Indonesia. The data was collected through observations and in-depth interviews. The findings indicate that CLIL is implemented based on the 4C’s framework (communication, content, cognition, and culture) in all stages of learning activity (pre-while-post activity). Although CLIL is theoretically mentioned to be applied flexibly, the teacher emphasized the particular pattern: communication comes first, followed by content, continued by cognition, and last is culture, with the intention of accommodating and facilitating both students’ cognitive and affective sides, as well as learning engagement and interactivity during remote learning in the pandemic era. Some challenges are also reported to emerge, but the school's support has helped this approach be executed successfully. This study implies that CLIL can provide ideal outcomes when all components of the school work together to be ready to execute it, despite the obstacles that grow in cyberspace that hamper face-to-face learning.